Chemical investigation and effects of the tea of Passiflora alata on biochemical parameters in rats - Doyama, J. T.; Rodrigues, H. G.; Novelli, ELB; Cereda, E.; Vilegas, Wagner [UNESP] (Elsevier B.V., 2005)
Passiflora alata (Passifloraceae) is a native plant from the South-America tropical forest that provides a much apreciated fruit known as maracuja-doce. Although tea of the leaves of Passiflora alata is used in folk medicine as a sedative and tranquilizer, there are no investigations about its effects on biochemical parameters in blood or from its major chemical composition. The purpose of this study was to evaluate the effects of the tea of the leaves of Passiflora alata on biochemical parameters (antioxidant system, glucose and cholesterol levels) and to perform a phytochemical investigation of the tea. We isolated and identified two saponins and five C-glycosylflavones derived from apigenin, luteolin and chrysoeriol. Three of them are new in this species. Passiflora alata extract was administrated orally in rats at dose of 1000 mg/kg and it was observed an increase in high-density lipoprotein level (HDL-cholesterol). (C) 2004 Elsevier B.V.. All rights reserved.
Keywords: Passiflora alata; saponins; flavonoids; medicinal plant; HDL-cholesterol